UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA MATERI TEKS IKLAN TERHADAP PENGGUNAAN MEDIA GAMBAR FOTOGRAFI KELAS VIII-4 SMP NEGERI 7 MEDAN TAHUN PEMBELAJARAN 2017-2018 - Titi Silaniasti Pasaribu (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The purpose of this study was to increase student interest in learning advertising text and to find out student learning outcomes in advertising text using photographic image media. The method used by the author in this research is quantitative method. The data collection techniques used in the implementation of this study were observation, and student learning outcomes tests on advertising texts in Indonesian subjects. Based on the research results, the ability to understand ad text has reached 75% (the number of students who have excellent abilities with good abilities, namely 42.42 + 33.33 = 75%). Meanwhile, 27.27% were students with sufficient abilities. the result is 75% already have the ability to understand ad text, it can be concluded that the ability to understand students' ad text is good.